2010
DOI: 10.1002/mabi.200900451
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Assessment of Insulating Silicone Polymer Coatings Using an in vitro Glial Scar Assay

Abstract: Vapor-deposited silicone coatings are attractive candidates for providing insulation in neuroprosthetic devices owing to their excellent resistivity, adhesion, chemical inertness and flexibility. A biocompatibility assessment of these coatings is an essential part of the materials design process, but current techniques are limited to rudimentary cell viability assays or animal muscle implantation tests. This article describes how a recently developed in vitro model of glial scar formation can be utilized to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
(129 reference statements)
0
25
0
Order By: Relevance
“…[19][20][21] Among them, coating the electrode surfaces with biocompatible or bio-inert polymers can be an effective strategy to shield the foreign electrode materials and reduce astrocyte activation. [22][23][24][25][26][27][28][29] However, these coatings resulted in substantial increase in electrical impedance aer the surface modication and/or did not adequately reduce the glial response. [22][23][24][25][26][27][28][29] However, these coatings resulted in substantial increase in electrical impedance aer the surface modication and/or did not adequately reduce the glial response.…”
mentioning
confidence: 99%
“…[19][20][21] Among them, coating the electrode surfaces with biocompatible or bio-inert polymers can be an effective strategy to shield the foreign electrode materials and reduce astrocyte activation. [22][23][24][25][26][27][28][29] However, these coatings resulted in substantial increase in electrical impedance aer the surface modication and/or did not adequately reduce the glial response. [22][23][24][25][26][27][28][29] However, these coatings resulted in substantial increase in electrical impedance aer the surface modication and/or did not adequately reduce the glial response.…”
mentioning
confidence: 99%
“…While other in vitro platforms have focused on studying how neurons are affected by CSPG and laminin gradients [18], chemically activated astrocytes [45], mechanically stretched co-cultures of astrocytes and fibroblasts [46], or mixed glial cell cultures [47], this biomaterial platform was designed to specifically study how neurite extension was affected by astrocyte morphological transitions. Along with other groups, we have previously shown that astrocytes cultured on aligned substrates have altered functions that mostly appear to be supportive of neuron survival and growth when compared to astrocytes cultured on smooth, isotropic substrates [34,3941,5153].…”
Section: Discussionmentioning
confidence: 99%
“…4). Direct contact models involve either seeding cells directly on a biomaterial surface (cell adhesion models) [75] or bringing a material into contact with cells grown on a control surface (implant mimicking models) [36,76,77]. Both direct contact models allow for investigation of cellular reaction to material surfaces, and of how the cell contact can modify the surface [78].…”
Section: In Vitro Cell Culture Models For Assessing Intracortical Impmentioning
confidence: 99%
“…There are a number of short-term interactions that can be assessed from in vitro blood and peripheral immune cell models; these are relevant to the integration and performance of materials and microdevices within the human body and CNS [23,76]. More research into how microglia modify these reactions will give immune cell and blood studies more relevance to biomaterials and devices developed for neuroprosthetic applications.…”
Section: Monocyte/macrophage Culturesmentioning
confidence: 99%